Impact of the Marker Set Configuration on the Accuracy of Gait Event Detection in Healthy and Pathological Subjects - Visscher, Rosa M. S.; Freslier, Marie; Moissenet, Florent; Sansgiri, Sailee; Singh, Navrag B.; Viehweger, Elke; Taylor, William R.; Brunner, Reinald (Frontiers in Human Neuroscience, 2021)
For interpreting outcomes of clinical gait analysis, an accurate estimation of gait events, such as initial contact (IC) and toe-off (TO), is essential. Numerous algorithms to automatically identify timing of gait events have been developed based on various marker set configurations as input. However, a systematic overview of the effect of the marker selection on the accuracy of estimating gait event timing is lacking. Therefore, we aim to evaluate 1) if the marker selection influences the accuracy of kinematic algorithms for estimating gait event timings and 2) what the best marker location is to ensure the highest event timing accuracy across various gait patterns. 104 individuals with cerebral palsy (16.0±8.6y) and 31 typically developing controls (age 20.6±7.8) performed clinical gait analysis, and were divided into two out of 8 groups based on the orientation of their foot, in sagittal and frontal plane at mid-stance. 3D marker trajectories of 11 foot/ankle markers were used to estimate the gait event timings (IC, TO) using 5 commonly used kinematic algorithms. Heatmaps, for IC and TO timing per group were created showing the median detection error, compared to detection using vertical ground reaction forces, for each marker. Our findings indicate that median detection errors can be kept within 7ms for IC and 13ms for TO when optimizing the choice of marker and detection algorithm towards foot orientation in midstance. Our results highlight that the use of markers located on the midfoot is robust for detecting gait events across different gait patterns.